The first Engkabang Jantong (Rubroshorea macrophylla) genome survey data - Chung, Hung Hui; Asmeralda Soh, Ai Leen; Melinda Lau, Mei Lin; Gan, Han Ming; Sim, Siong Fong; Leonard Lim, Whye Kit (Elsevier Inc., 2024)
The engkabang jantong (Rubroshorea macrophylla) is one of the most indispensable tree species for reforestation due to its high survival rate and rapid growth rate. Due to relatively low genetic interest of this tree species, its genomic landscape has since faced scarcity, impeding our further elucidation on genes that are involved in expressing its aforementioned superior properties. In this study, we performed genome survey and microsatellite analysis of engkabang jantong. Based on the results, the estimated genome size of this species is 312,071,515 bp with 18.43% repeated sequences and 1.16% heterozygosity. BUSCO analysis unearthed that 83.5% of the contigs are single-copy genes whereas 12.7% of them are duplicated. Only 2.8% and 1% of them are fragmented and missing respectively. The short-read sequencing results obtained from the Illumina platform in this study will be essential to complement the Nanopore long-read sequencing results in hybrid genome assembly endeavors in the near future.